French Peasants in Revolt : The Insurrection of 1851 - Margadant, Ted W. (Book collections on Project MUSE., 2008)
The triumphant rise of Louis Napoleon Bonaparte over his Republican opponents has been the central theme of most narrative accounts of mid-nineteenth-century France, while resistance to the coup d'etat generally has been neglected. By placing the insurrection of December 1851 in a broad perspective of socioeconomic and political development, Ted Margadant displays its full significance as a turning point in modern French history. He argues that, as the first expression of a new form of political participation on the part of the peasants, resistance to the coup was of greater importance than p.